2005
DOI: 10.1097/00006982-200510000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone Acetonide With Vitrectomy for Treatment of Macular Edema Associated With Branch Retinal Vein Occlusion

Abstract: An intraoperative injection of TA in combination with PPV has the potential to facilitate the absorption of macular edema associated with BRVO. In addition, residual or recurrent macular edema can be treated with additional sub-Tenon capsule injections of TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
2
23
1
2
Order By: Relevance
“…In a prospective nonrandomized comparative study on 11 eyes with CRVO receiving an intravitreal injection of TA, compared with 6 eyes of a control group without intravitreal injection of TA, the gain in visual acuity was significantly (p = 0.003) higher in the study group [103]. This confirms results of other reports on the beneficial effect of intravitreal TA on macular edema and visual acuity in patients with CRVO [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99]. The results additionally suggest that the increase in visual acuity after IVTA injection may not last permanently in eyes with CRVO.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemasupporting
confidence: 79%
See 2 more Smart Citations
“…In a prospective nonrandomized comparative study on 11 eyes with CRVO receiving an intravitreal injection of TA, compared with 6 eyes of a control group without intravitreal injection of TA, the gain in visual acuity was significantly (p = 0.003) higher in the study group [103]. This confirms results of other reports on the beneficial effect of intravitreal TA on macular edema and visual acuity in patients with CRVO [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99]. The results additionally suggest that the increase in visual acuity after IVTA injection may not last permanently in eyes with CRVO.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemasupporting
confidence: 79%
“…In an exponentially increasing number of case series studies and nonrandomized comparative studies, IVTA has been used for the treatment of BRVO [80,81,82,83,84,85,86,87,88,89,90,91,92,251]. Özkiris et al [86] evaluated the efficacy of IVTA injection on persistent macular edema in BRVO that failed to respond to previous laser photocoagulation.…”
Section: Clinical Studies: Ta As Drug Treatment For Macular Edemamentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining corticosteroids were chosen to have a selection of corticosteroids with a broad span of lipophilicity and solubility. Because therapy of back of the eye diseases requires chronic dosing, corticosteroids are typically administered as suspensions (Tsujikawa et al, 2005;Lin et al, 2007;Toda et al, 2007;Shima et al, 2008). Furthermore, injection of a small volume at the soluble concentrations of corticosteroids was inadequate in rat in vivo studies to detect drug levels in the back of the eye tissues.…”
Section: Transscleral Retinal Delivery Of Corticosteroidsmentioning
confidence: 99%
“…There is limited knowledge regarding IOP changes after intravitreal injection or short-term systemic application of steroids in vitrectomized eyes. Tsujikawa et al 27 reported an IOP increase of 421 mm Hg in 9 of 17 (53%) vitrectomized eyes after IVTA injection of 10 mg. In our study, no statistically significant elevation of the IOP after vitrectomy was seen in both groups.…”
mentioning
confidence: 99%